Implementation of Digital Marketing Strategies by Village-Owned Enterprises (BUMDes) in Village Tourism Management - Adhi Susano (PT Publikasiku Academic Solution, 2024)
The development of village tourism has become an important solution in boosting the local economy and preserving local culture. Village-owned enterprises (BUMDes) play a crucial role in managing this initiative. In the current digital era, the utilization of digital marketing strategies is increasingly important in enhancing the attractiveness and visitor arrivals to village tourism destinations. This research aims to analyze the implementation of digital marketing strategies used by BUMDes in managing village tourism. The research method used is a case study of several village tourism destinations managed by BUMDes in various regions. Data were collected through direct observation of digital marketing activities conducted. Data analysis was performed using a descriptive qualitative approach to identify effective digital marketing strategies. The research outcomes indicate that BUMDes can adopt various digital marketing strategies to manage village tourism, including the use of social media, creating engaging digital content, collaborating with digital influencers, and utilizing online booking platforms. These findings provide valuable insights for BUMDes managers, local governments, and other stakeholders in developing effective digital marketing strategies for village tourism management in this digital era. The research also highlights the challenges and opportunities faced by BUMDes in adopting and implementing digital marketing strategies.